2014
DOI: 10.1371/journal.pone.0108112
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Effect of Phytosterols in Experimental Murine Colitis Model: Prevention, Induction, Remission Study

Abstract: Phytosterols, besides hypocholesterolemic effect, present anti-inflammatory properties. Little information is available about their efficacy in Inflammatory Bowel Disease (IBD). Therefore, we have evaluated the effect of a mixture of phytosterols on prevention/induction/remission in a murine experimental model of colitis. Phytosterols were administered x os before, during and after colitis induction with Dextran Sodium Sulfate (DSS) in mice. Disease Activity Index (DAI), colon length, histopathology score, 18F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 70 publications
2
60
0
Order By: Relevance
“…In addition to betulinic acid, b-sitosterol also exhibited inhibitory influence on TNBS-induced UC in mice through inhibition of proinflammatory cytokines and cycloxygenase (COX-2) enzymes (Lee et al 2012). Recently b-sitosterol showed preventive effect on dextran sodium sulphate-induced colitis through anti-inflammatory action (Aldini et al 2014). This evidence suggests that the anticolitic effect of tuber extracts may be due to the presence of betulinic acid and b-sitosterol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to betulinic acid, b-sitosterol also exhibited inhibitory influence on TNBS-induced UC in mice through inhibition of proinflammatory cytokines and cycloxygenase (COX-2) enzymes (Lee et al 2012). Recently b-sitosterol showed preventive effect on dextran sodium sulphate-induced colitis through anti-inflammatory action (Aldini et al 2014). This evidence suggests that the anticolitic effect of tuber extracts may be due to the presence of betulinic acid and b-sitosterol.…”
Section: Discussionmentioning
confidence: 99%
“…The DAI was calculated for each animal, as reported previously (18). Briefly, the DAI was determined by combining the scores assigned for body weight loss, stool consistency and stool blood, with the mean of the three values deemed the DAI.…”
Section: Evaluation Of Disease Activity Index (Dai)mentioning
confidence: 99%
“…Phytosterols have also been reported to have anti-inflammatory effects in commonly used animal models for colitis 59 . It was reported that β-sitosterol attenuates high-fat diet-induced colitis in C57BL/6J mice 5 .…”
Section: Introductionmentioning
confidence: 99%